2011
DOI: 10.1021/jp205433j
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Structure H Clathrate Hydrate Formers

Abstract: Hexamethyleneimine, 1-methylpiperidine, 2-methylpiperidine, 3-methylpiperidine, and 4-methylpiperidine as isomers of C6H13N were revealed as new sH clathrate hydrate forming molecules. They show fully soluble characteristics to water, whereas already known sH formers such as methylcyclohexane and 2,2-dimethylbutane (neohexane) are immiscible or very slightly soluble to water. The L–H–V equilibrium P–T behavior of these new sH clathrate hydrates shows a tendency to shift to much milder conditions than already k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
57
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 20 publications
10
57
0
Order By: Relevance
“…The model is classical; it neglects delocalization and zero point energies which have been shown to have significant consequences for the adsorption of helium, hydrogen, and neon on coronene 30,37-41 and other carbonaceous systems. [49][50][51] Even so, we expect that the classical structures discussed here will have some bearing on the spatial probability distribution of the actual quantum mechanical system. It has been shown, for example, that a classical description of (neutral or cationic) He 32 C 60 which has a commensurate solvation shell captures essential features of more rigorous quantum mechanical descriptions [49][50][51] although discrepancies become more significant for incomplete and incommensurate shells.…”
Section: Discussionmentioning
confidence: 99%
“…The model is classical; it neglects delocalization and zero point energies which have been shown to have significant consequences for the adsorption of helium, hydrogen, and neon on coronene 30,37-41 and other carbonaceous systems. [49][50][51] Even so, we expect that the classical structures discussed here will have some bearing on the spatial probability distribution of the actual quantum mechanical system. It has been shown, for example, that a classical description of (neutral or cationic) He 32 C 60 which has a commensurate solvation shell captures essential features of more rigorous quantum mechanical descriptions [49][50][51] although discrepancies become more significant for incomplete and incommensurate shells.…”
Section: Discussionmentioning
confidence: 99%
“…[36] ReaxFF has also been used to investigate fracture properties of materials such as silicon, [30,37] graphyne, [38,39] graphene, [22,29] and Fe/Ni/Al. [40] While ReaxFF has been shown to accurately reproduce fracture properties of some materials, it is unclear if the most recent C/H/O parameter set of Chenoweth et al [17] (henceforth referred to as the Chenoweth C/H/O parameter set) is appropriate for simulating fracture behavior in carbon-based systems. Because of the complex nature of fracture and the relative novelty of ReaxFF, specific modeling details and simulation parameters for predicting crack initiation and growth in carbon-based materials have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%
“…More experimental data would be required for hydrate equilibrium conditions of 4-mMPL, but it can be concluded that 4-mMPL might be used to inhibit the hydrate formation. On the basis of several studies on phase stability (Lee et al, 2010;Shin et al, 2011;Jin et al, 2013), most binary sH hydrate systems require milder conditions to form gas hydrate compared with the pure CH 4 hydrate. The phase stability of gas hydrates is known to be affected by the molecular size and shape of the LMGS as well as guest-host interactions.…”
Section: Resultsmentioning
confidence: 99%
“…A large number of studies have been carried out to identify phase equilibrium conditions, formation kinetics, and structural characteristics (Lee et al, 2010;Seo et al, 2010). Moreover, new LMGSs enclosed in sH hydrates with CH 4 gas are being explored for gas storage application and separation media, since sH hydrates commonly have superior storage capacity and thermodynamic stability compared to sI and sII hydrates (Shin et al, 2011;Jin et al, 2013;Strobel et al, 2008). Recently, the gas hydrate has become one of the major issues in flow assurance, as it may block flowlines during the production and transportation of petroleum fluids (Sloan, 2005).…”
Section: Introductionmentioning
confidence: 99%